Role of screening colonoscopy for colorectal tumors in Helicobacter pylori-related chronic gastritis with MDM2 SNP309 G/G homozygous: A prospective cross-sectional study in Thailand - Tongtawee, Taweesak; Simawaranon, Theeraya; Wattanawongdon, Wareporn (Turkish Journal of Gastroenterology, 2018)
Abstract Background/Aims: Helicobacter pylori infection is a risk factor for gastric cancer and colorectal cancer (CRC). MDM2 SNP309 G/G homozygosity is known to be the genetic background that influences the severity of inflammation in the gastric mucosa, and it corresponds to CRC development. We examined the role of screening colonoscopy in H. pylori-related chronic gastritis and the association of patients who have MDM2 SNP309 G/G homozygosity and advanced colorectal neoplasia (CRN) susceptibility. Materials and Methods: A prospective cross-sectional study was used to investigate H. pylori-related gastritis in 331 consecutive asymptomatic patients who had MDM2 SNP309 G/G homozygosity and who were enrolled from November 2014 to July 2017. The MDM2 SNP309 polymorphism was genotyped by real-time PCR hybridization probe assay. Results: Totally, there were 331 patients with H. pylori-related gastritis, of whom 39 (8.76%) had advanced CRN. The H. pylori-positive group comprised 180 patients (54.36%). H. pylori infection was associated with advanced CRN (OR: 2.09, 95% CI: 1.56-2.80; p=0.01) and had an increased risk of advanced CRN (OR: 4.24, 95% CI: 1.76-5.21; p=0.01) after adjusting for confounding factors. Patients with H. pylori infection had a significantly increased risk of high-grade dysplasia or invasive adenocarcinoma (OR: 2.96, 95% CI: 1.48-4.17; p=0.03). Conclusion: Chronic gastritis patients infected with H. pylori and who had MDM2 SNP309 G/G homozygosity had an increased risk of advanced CRN, particularly high-grade dysplasia including invasive adenocarcinoma. Screening colonoscopy in these patients might benefit colorectal polyp diagnosis and prevention and early CRC treatment in the Thai population. Cite this article as: Tongtawee T, Simawaranon T, Wattanawongdon W. Role of screening colonoscopy for colorectal tumors in Helicobacter pylori-related chronic gastritis with MDM2 SNP309 G/G homozygous: A prospective cross-sectional study in Thailand. Turk J Gastroenterol 2018; 29: 555-60.